2011
DOI: 10.1007/s13530-011-0075-4
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression analysis identifies potential biomarkers of phenanthrene in human hepatocytes (HepG2)

Abstract: Polycyclic aromatic hydrocarbons (PAHs) are ubiquious in the environment both as natural products and as environmental contaminants. Among PAHs, phenanthrene (PH) that is ubiquitously distributed throughout the environment was subjected in this study. Although environmental distribution and metabolism of PH have been well reported, there are only a few studies examined the expression of mRNA and their functions on PH-induced toxicity. A new paradigm in toxicity screening, toxicogenomic technology represents a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 21 publications
(23 reference statements)
1
7
0
Order By: Relevance
“…Early initiatives to use in vitro alternatives combined with transcriptomics for the prediction of toxicity have shown promising results 26,27 . Through previous studies in our laboratory, we confirmed toxicogenomic effects of several hazardous chemicals involved in inducing cancer or other diseases 28,29 .…”
Section: Discussionsupporting
confidence: 64%
“…Early initiatives to use in vitro alternatives combined with transcriptomics for the prediction of toxicity have shown promising results 26,27 . Through previous studies in our laboratory, we confirmed toxicogenomic effects of several hazardous chemicals involved in inducing cancer or other diseases 28,29 .…”
Section: Discussionsupporting
confidence: 64%
“…We have investigated the mechanism(s) of toxicity of PAHs and other environmental toxicants in human cell lines, based on alteration of gene expression. ( 25,26 ) In this study, we identified gene expression profiles induced by three PAHs in HepG2 cells using a 44K whole human oligonucleotide microarray. With a statistical cut‐off of ≥1.5‐fold change, the expression levels of 532 genes were commonly upregulated and those of 742 genes were commonly downregulated upon exposure to B[a]A, B[k]F, and IND (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Octanal concentrations were considered appropriate for microarray analysis due to the fact that such an exposure level gives meaningful outcomes in in vitro toxicogenomic studies on carcinogenesis and other toxicity in our research group. 36,43 Our results focused on microarray data, which indicated differential expression of inflammatory response genes after octanal exposure. Aldehyde-induced alterations in stress-responsive genes in the human respiratory system have been studied, 44 but the data regarding changes in cytokine expression are limited.…”
Section: Discussionmentioning
confidence: 99%